Short‐ and long‐term effects of tracking devices on the European Roller Coracias garrulus. (26th October 2015) - Rodríguez‐Ruiz, J.; Parejo, D.; de la Puente, J.; Valera, F.; Calero‐Torralbo, M. A.; Bermejo, A.; Catry, I.; Avilés, J. M.
Abstract : Tracking devices have contributed enormously to our knowledge of avian migration, although their effects on birds are controversial. Here, we study the short‐ and long‐term effects of deploying geolocators on European Rollers Coracias garrulus and assess the optimal weight of tracking devices to use. In nests in which both parents had geolocators, brood mass was lighter than in nests where only one or neither parent had a geolocator. The year‐to‐year recapture rate for Rollers tagged with geolocators was lower than that for control birds and the recapture rate in different populations was negatively related to the device‐to‐bird weight ratio, decreasing greatly when the weight ratio exceeded 2.5%.